Progressive Muscle Relaxation Reducing Blood Sugar Levels In Diabetes Mellitus Patients: Literature Review - Rochmah, Ardianti Fauziah; Muhith, Abdul; Zahro, Chilyatiz (Chakra Brahmanda Lentera Institute, 2023)
Background: Diabetes will cause many complications if it is not treated properly. Complex treatment for people living with diabetes will cause a person to experience stress, so not many sufferers comply with treatment to control blood sugar levels. This literature review aims to determine the reduction in blood sugar levels in diabetes mellitus sufferers with progressive muscle relaxation. Methods: The method used in this article is a literature review using journal databases from Science Direct, PubMed, and Google Scholar in the 2020-2023 time period with the keywords